Prevalence of intestinal parasitic infection and socioeconomic characterization of Brazilian fishing colonies (Research, Society and Development, 2021)
Overview: artisanal fishing is an activity that can harm workers' health, as it exposes fishermen to various weather conditions and high physical effort, leaving them susceptible to infectious diseases, such as intestinal parasites. Objective: identify the highest prevalence of infection by intestinal parasites in fishermen in the northern region of Brazil. Methods: descriptive cross-sectional study, in accordance with the guidelines of the STROBE Declaration, carried out in two fishing colonies in Northern Brazil. Results: we identified the following protozoa: Escherichia Coli, Endolimax Nana, Escherichia Coli, Giardia Lamblia, Iodamoeba Bustschlii. No positive samples for helmintoses were found. Conclusion: among the species of enteroparasitosis investigated in 2019, in the North of Brazil, there was a prevalence (> 50%) of Endolimax Nana in parasitized fishermen.